2017
DOI: 10.3390/ma10060619
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Fibre-Reinforced Biofoam for Structural Applications

Abstract: Traditionally, polymers and macromolecular components used in the foam industry are mostly derived from petroleum. The current transition to a bio-economy creates demand for the use of more renewable feedstocks. Soybean oil is a vegetable oil, composed mainly of triglycerides, that is suitable material for foam production. In this study, acrylated epoxidized soybean oil and variable amounts of cellulose fibres were used in the production of bio-based foam. The developed macroporous bio-based architectures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Acrylated epoxidized soybean oil (AESO) finds increasing uses in partially biobased thermosetting acrylic and unsaturated polyester resins. Different research works have focused on the development of thermosetting resins with AESO directly [ 51 ] or with different copolymers, such as methacrylated eugenol [ 52 ], N-vinyl-2-pyrrolidone [ 53 ], isosorbide methacrylate [ 54 ], rosin-based acrylamide [ 55 ] and so on, with potential uses in composites. AESO has also been reported as additive in toughened PLA formulations [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylated epoxidized soybean oil (AESO) finds increasing uses in partially biobased thermosetting acrylic and unsaturated polyester resins. Different research works have focused on the development of thermosetting resins with AESO directly [ 51 ] or with different copolymers, such as methacrylated eugenol [ 52 ], N-vinyl-2-pyrrolidone [ 53 ], isosorbide methacrylate [ 54 ], rosin-based acrylamide [ 55 ] and so on, with potential uses in composites. AESO has also been reported as additive in toughened PLA formulations [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the commercial epoxies come from petroleum, in the last years, new environmentally-friendly epoxies from vegetable oils have been proposed as eco-friendly adhesives and composite matrices [ 16 , 17 , 18 ]. Obradovic et al reported the potential of acrylated epoxidized soybean oil (AESO) in producing industrial foams with cellulose reinforcements [ 19 ]. Even more, Arevalo et al have proposed the use of the self-binding capability of cellulose to obtain binderless fibreboards by hot-pressing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These polar groups provide the possibility for the formation of hydrogen bonds between AESO and fillers [80]. Thermoplastic polyurethane [81], microcrystalline cellulose (MCC) [80] and cellulose fiber [82] are the common reinforcements worth investigation for poly(acrylated epoxidized soybean oil)(PAESO). The interaction between PAESO and polyurethane can be enhanced by the formation of hydrogen bonds between hydrophilic functional groups from both of the two components which give rise to the result of improving the toughness and increasing the elongation of PAESO [81].…”
Section: Thermal Initiation Of Aesomentioning
confidence: 99%
“…As a green filler, microcrystalline cellulose will increase the density, hardness, flexural strength and modulus of the material without decreasing the bio-based content [80]. Cellulose-reinforced PAESO can also be successfully made into biobased foams with enhanced mechanical properties, which shows the great potential to replace petroleum-based foams [82].…”
Section: Thermal Initiation Of Aesomentioning
confidence: 99%